Innovation of the Fishery Licensing Integration System (SIRIP) Program for the Marine and Fisheries Office of East Java Province - Renata Nanda Swastika; Vidya Imanuari Pertiwi (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Obstacles in licensing services experienced by fishermen and business actors prove that there is a need to improve the quality of public service systems and the quality of state civil servant resources. Responding to this, the East Java Provincial Marine and Fisheries Service developed a digital-based public service innovation, namely the Fisheries Licensing Integration System (SIRIP) program innovation. The purpose of this study is to describe the innovation of the SIRIP program implemented within the scope of the East Java Provincial Marine and Fisheries Service and to identify supporting and inhibiting factors in the implementation of the SIRIP program. This study uses a qualitative research method with a case study approach through interviews, observations, documentation and literature studies based on the theory of innovation success factors (Arundel et al., 2019). The results of the study show that from the governance and innovation indicators, the regulatory system or policies used are in accordance with the policies that have been determined. The source of innovation indicators come from internal and external parties to the agency. The culture of innovation changes the mechanism of shipping and fisheries licensing to digital technology. Innovation capabilities and tools have appropriate facilities and infrastructure and are supported by competent human resources. The objectives, results, drivers and obstacles of the SIRIP website program have not been maximized in achieving the expected objectives. Collecting single information data on updates and transitions from the SIMKADA website to a single website, namely SIRIP Keywords: Integration System, Marine and Fisheries, Program Innovation.